How is the Statistical Literacy of Upper Secondary Students Based on Gender Differences? - Risqi, Erlyanna Nur; Ekawati, Rooselyna (Universitas Negeri Surabaya, 2020)
The study aimed to describe the statistical literacy of upper secondary student based on gender differences. There are a gap between female sex is not necessarily feminine and conversely male students are not necessarily masculine, there is a possibility that the person is of type androgyny or indistinguishable. The study was conducted in four students with different gender type that is masculine type, feminine type, androgynous type, and indistinguished type. Data was collected using the Statistical Literacy Test, developed based on the statistical framework about statistical literacy ability with indicator of understanding data, interpreting data, and communicating data. The result with quantitave and qualitative research revealed significant differences statistical literacy based on gender differences. In this study shows that the feminine type has the highest statistical literacy skill between other gender types in understanding data, interpreting data, and communicating data. In understanding data, the feminine type can read data and supported with arguments that are easily understood. In interpreting data, feminine type are able to make predictions of future possibilities, can determine the value of increase and decrease in data, able to think critically about the data presented and able to make conclusions based on the data. But, in communicating data feminine type make mistakes in changing the shape of data from graphs to table forms. Then, statistical literacy ability followed by androgynous type. Then, the lowest statistical ability in the masculine type and the cannot be distinguished type.